Spatial Dynamics of Vegetation Index Changes in the Weda Nickel Mining Area, Halmahera Island, Indonesia - Rakuasa, Heinrich; Khromykh, Vadim V (Journal of Scientific Insights, 2026)
Nickel mining in Weda, Halmahera Island, is one of the largest nickel mines in Indonesia, and its activities impact changes in vegetation indices and cover in the area. The research uses Landsat 8 satellite imagery from 2019, 2022, and 2025 with the NDVI algorithm to analyse changes in vegetation index values and vegetation cover. The research results show that the NDVI values for 2019 are the lowest at -0.233774 and the highest at 0.999903; for 2022, the lowest is -0.369486 and the highest is 0.799867; and for 2025, the lowest is -0.369486 and the highest is 0.530372. The NDVI values were then classified into 4 vegetation cover classes: active mining areas, sparse, moderate, and dense vegetation. The active mining area in 2019 was 1.27 km², in 2022 it was 11.91 km², and in 2025 it was 18.20 km². Sparse vegetation in 2019 covered 5.73 km², in 2022 it covered 6.03 km², and in 2025 it covered 8.07 km². Moderate vegetation in 2019 covered 5.72 km², in 2022 it covered 2.68 km², and in 2025 it covered 2.21 km². Dense vegetation in 2019 covered 522.64 km², in 2022 it covered 515.35 km², and in 2025 it covered 507.20 km². The presentation of the mining area continues to increase every year. The results of this research are expected to be used for continuous monitoring to ensure compliance with environmental standards and support rehabilitation programmes in Weda and other tropical mining areas.